MODEL PEMBELAJARAN PASSING FUTSAL MENGGUNAKAN METODE COOPERATIVE TIPE STUDENT TEAMS-ACHIEVEMENT DIVISION DI SMP PANDU SISWA - Chairul Imam; Slamet Sukriadi; Eko Prabowo (IKIP PGRI Pontianak, 2022)
This research produces a futsal passing learning model product using a cooperative type of student teams-achievement division at SMP Pandu Siswa, aiming to provide variations of the passing learning model and also to provide students with passing technique skills. This study uses a research and development method (Research and Development) which refers to the ADDIE model. The product is validated by learning experts, futsal experts, PJOK teachers. From the results of research and development, the researchers managed to get 7 (seven) products for the futsal passing learning model. The data was obtained from the results of the validation test of the passing learning model for students with experts. The results of this study are expected to be a reference material for teachers in designing learning programs and can improve passing skills and knowledge, especially at SMP Pandu Siswa.